Adjectivization in Azerbaijani and Arabic languages - Hasameddin, Lala Aliguliyeva (Conrado, 2024)
ABSTRACT The process of enriching language vocabulary occurs in two fundamental directions. Firstly, new words emerge through the language's inherent potential, reflecting its internal linguistic capabilities and secondly, vocabulary enrichment can result from the incorporation of lexicon from other languages, influenced by external factors. This article focuses particularly on the development of word creativity through the internal capacities of language, which involves the transformation of words from one part of speech to another through various morphological-syntactic, lexical-syntactic, and lexical-semantic processes, known as conversion. Throug this phenomenon it is possible is to uncover derivational meanings and paradigms of word-forming types. As the subject of conversion is to huge, in this research we will focus mainly in adjectivization in Azerbaijani and Arabic languages. It was found that in both languages, adjectivization of participles based on verbs emerges as an extensive and productive method. In the research, it is analyzed how this process often involves the loss of grammatical categories such as manner, tense, and voice functions of the participles, or their alteration, including the change or loss of the governing verbs.